Combining Abilities of Carcass Traits among Pure and Crossbred Meat Type Chickens - Adebambo, A.O.; Adeleke, M.A.; Whetto, M.; Peters, S.O.; Ikeobi, C.O.N.; Ozoje, M.O.; Oduguwa, O.O.; Adebambo , Olufunmilayo A. (International Journal of Poultry Science, 2010)
Two hundred and ninety five cocks and two hundred and ninety nine hens were selected from a diallel combination of four breeds of chickens; [Anak Titan (A), Alpha (B), Giriraja (G) and Normal indigenous (N) chickens] at 12 weeks of age in a broiler improvement program for carcass analysis. The following data were collected in percentages: economically important traits = Live weight (g), Plucked weight, Eviscerated weight, Carcass yield, Abdominal fat percentage, Breast yield, Thigh yield, Drumstick yield; survival organs = Wing yield, Internal organ, Empty gizzard yield, Heart yield, Lung yield, Kidney yield, Liver yield. Analyses of variance of carcass traits show that sire and dam genotype significantly (p<0.05) affected carcass traits. Anak Titan sires and dams performed best in economically important traits, while N and B performed better in survival organs. Sex had significant (p<0.05) effect only on live weight with cocks having higher values of 979.55±56.62 and hens 879.6±34.18. Results of diallel analysis to test for general and specific combining abilities of breeds on traits showed that additive genetic effects were important in determining economically important traits, indicative that improvement can be achieved by selection. Dominance effects were important in control of survival organs, indicative of improvement by crossbreeding. Estimates of GCA for carcass traits show that Anak Titan had highest general combining ability for most of the carcass parameters while the least values were found among Alpha chickens. Estimates of SCA for carcass parameters showed AN cross generally had highest SCA for most of the carcass traits. Least SCA values for carcass parameters were generally recorded for AB crosses. It is recommended that an improvement process that involves all the breeds should be adapted using reciprocal recurrent selection or modifications of it.